Intraspecific variation in tree growth responses to neighbourhood composition and seasonal drought in a tropical forest. (16th August 2020) - Yang, Jie; Song, Xiaoyang; Zambrano, Jenny; Chen, Yuxin; Cao, Min; Deng, Xiaobao; Zhang, Wenfu; Yang, Xiaofei; Zhang, Guocheng; Tang, Yong; Swenson, Nathan G.
Abstract: Functional traits are expected to provide insights into the abiotic and biotic drivers of plant demography. However, successfully linking traits to plant demographic performance likely requires the consideration of important contextual and individual‐level information that is often ignored in trait‐based ecology. Here, we modelled 8 years of growth from 1, 138 individual trees in 36 tropical rain forest species. We compared models of tree growth parameterized using individual‐level versus species mean trait data. We also compared models that considered regional climatic, local biotic and whole‐plant allocation contexts to those that do not. Our analyses show that growth models parameterized using individual‐level trait information outperformed those that used species mean trait information and that these models often contradicted one another indicating that the common practice of using species mean trait data requires more scrutiny. Additionally, we found that models including climatic, biotic and allocation contexts outperformed those that did not and provided nuanced insights into the drivers of tree growth in a tropical forest. Synthesis . Here we have shown that the development of models of tree demographic performance upon the basis of traits can be improved through a consideration of individual‐level trait variation as well as phenotypic and climatic contexts. We highlight that our ability to understand the drivers of tree population and community structure and dynamics in current and in future climates will be limited if contextual and individual‐level data remains understudied. Abstract : The plant ecology literature has been rapidly accumulating functional trait and neighbourhood modelling studies for the last decade. A surprising outcome is that these studies often find weak results. Here we provide the first study to our knowledge that utilizes individual‐level trait data while simultaneously considering the biotic and temporally varying climatic contexts an individual tree experiences to model fine‐scale tree growth. Importantly, the results cast doubt on the utility of widely utilized approaches that do not consider how trait‐based biotic interactions are mediated by trait–climate interactions and that rely on species‐level aggregation of trait data. 摘要: 功能性状常被用来揭示生物和非生物因子如何驱动植物的种群动态。但是，当前大部分研究忽视了植物个体表现及其周围环境的信息。 本研究使用广义线性混合模型，对热带雨林中36个树种共1, 138个树种个体的8年生长情况进行了长期追踪。通过比较物种水平和个体水平功能性状的模型拟合效果，验证含有区域气候因子、局域尺度的生物因子和包含植物整合性状的模型具有更好的拟合结果。 研究结果揭示，包含个体水平性状的模型优于长期使用的物种水平性状的模型。由于两种模型的结果存在一定的矛盾，表明使用物种平均性状的研究需要更加谨慎。 研究结果强调树种个体水平整合功能性状及其所处环境因子对树种生长解释的重要性。如果忽视环境和个体水平在种群动态中的作用，我们对当前和未来全球变化背景下，树木种群、群落结构和动态驱动力的理解将极其有限。